Os conceitos normatizados pela legislaçao e a interpretaçao da estrutura agrária e fundiária no Brasil - Talaska, Alcione; Etges, Virginia Elisabeta (2015)
Considering agrarian legislation of the last 50 years, this article expressed the objetive to identify and describe the concepts that are used for the characterization and understanding of the conformation of the brazilian agrarian space. We noted, in this context, a process of change in the laws, which suppressed the concepts of latifundio (landlordism) and minifundio (small parcels property), which created concepts of small property, of average property, of productive property and of family agriculture, but which not considered other important definitions: large farms and paternal agriculture. This substitution of interpretative concepts limits the understanding of the brazilian agrarian dynamics, especially if we consider the analysis of contradictory process of development capitalism in the field, in Brazil.
Considerando a legislação agrária dos últimos 50 anos, este artigo expressa o objetivo de identificar e descrever os conceitos que são utilizados para a caracterização e compreensão do espaço agrário brasileiro. Evidenciamos, nesse contexto, um processo de modificação nas leis, que suprimiu os conceitos de latifúndio e minifúndio, que criou conceitos de pequena e média propriedade, propriedade produtiva e agricultura familiar, mas que ignorou a elaboração de outras importantes definições: grande propriedade e agricultura patronal. Essa substituição dos conceitos interpretativos limita a compreensão da dinâmica agrária brasileira, especialmente, se levarmos em conta o processo contraditório do desenvolvimento do capitalismo no campo, no Brasil.
Keywords: Concepts; Agrarian legislation; Agrarian structure; Brazil; Conceitos^lpt; Legislaçao agrária; Estrutura agrária; Brasil